Identification of the Characteristics of Phytochemical Compounds in Microalgae Extracts - Sevilla Gita Raissa; Dedin Finatsiyatul Rosida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Microalgae are a source of bioactive compounds with potential for development as functional food ingredients. The effectiveness of bioactive compound extraction is influenced by the extraction method and the type of solvent used. This study aimed to determine the effect of microalgal species (Spirulina sp., Chlorella sp., and Nannochloropsis sp.) and solvent types (ethanol, methanol, and acetone) on the yield and phytochemical profile of the extracts produced using the Ultrasound-Microwave Assisted Extraction (UMAE) method. The study employed a factorial Complete Randomized Design (CRD) with two factors—microalgal species and solvent type—each replicated twice. Phytochemical screening results showed that Spirulina sp. extracts consistently contained alkaloids, phenols, flavonoids, saponins, tannins, and terpenoids in all solvents but did not contain steroids. Chlorella sp. extracts exhibited a similar phytochemical profile, except that tannins were not detected in the acetone extract. Meanwhile, Nannochloropsis sp. extracts showed variations in secondary metabolite content, with flavonoids and tannins detected only in the methanol extract. The results of this study indicate that the combination of microalgal species and solvent type influences both the yield and the phytochemical profile of the extracts produced via the UMAE method.